A two‐dimensional zinc(II) coordination polymer based on mixed dimethyl succinate and bipyridine ligands: synthesis, structure, thermostability and luminescence properties. Issue 4 (17th March 2016) - Liu, Yang; Feng, Yong-Lan; Fu, Wei-Wei
Abstract : A two‐dimensional zinc(II) coordination polymer, based on 2, 2‐dimethylsuccinate and 4, 4′‐bipyridine coligands, was prepared under hydrothermal conditions and structurally characterized. The complex was also characterized by elemental, IR and thermogravimetric analyses. The luminescence properties were investigated and the compound exhibits a blue photoluminescence in the solid state at room temperature. Abstract : From the viewpoint of crystal engineering, the construction of crystalline polymeric materials requires a rational choice of organic bridging ligands for the self‐assembly process. Multicarboxylate ligands are of particular interest due to their strong coordination activity towards metal ions, as well as their various coordination modes and versatile conformations. The structural chemistry of dicarboxylate‐based coordination polymers of transition metals has been developed through the grafting of N‐containing organic linkers into carboxylate‐bridged transition metal networks. A new luminescent two‐dimensional zinc(II) coordination polymer containing bridging 2, 2‐dimethylsuccinate and 4, 4′‐bipyridine ligands, namely poly[[aqua(μ2 ‐4, 4′‐bipyridine‐κ 2 N : N ′)bis(μ3 ‐2, 2‐dimethylbutanedioato)‐κ 4 O 1, O 1′ : O 4 : O 4′ ;κ 5 O 1 : O 1, O 4 : O 4, O 4′ ‐dizinc(II)] dihydrate], [Zn2 (C6 H8 O4 )2 (C10 H8 N2 )(H2 O)]·2H2 O n, has been synthesized under hydrothermal conditions and characterized by single‐crystal X‐ray diffraction and elemental, IR and thermogravimetric analyses. In the structure, the 2, 2‐dimethylsuccinate ligands link linear tetranuclear Zn II subunits into one‐dimensional chains along the c axis. 4, 4′‐Bipyridine acts as a tethering ligand expanding these one‐dimensional chains into a two‐dimensional layered structure. Hydrogen‐bonding interactions between the water molecules (both coordinated and free) and carboxylate O atoms strengthen the packing of the layers. Furthermore, the luminescence properties of the complex were investigated. The compound exhibits a blue photoluminescence in the solid state at room temperature and may be a good candidate for potential hybrid inorganic–organic photoactive materials.